Political Identity Of Transmigrant Communities In Tanah Abang Village In Jambi Through Gamelan - Devy Kartikasari; A. M. Susilo Pradoko (Institut Seni Indonesia Denpasar, 2019)
This research is intended to discover the procurement process of gamelan musical instruments as an effort to preserve the identity of Javanese transmigrants community in Tanah Abang village, reviewing the idea to the benefit to the community and exploring the meaning and the social values that is implied by the existence of the gamelan used by the communities to learn karawitan. The research was carried out in the Tanah Abang Jambi village, with the pengrawit and trainers as the objects, and the informants, through interview, of this research were the head of the Tanah Abang village, karawitan coach, pengrawit, and those who was part of the agent of change. The data taken was in the form of field-notes which were processed in such a way and sorted into an intact data that was easily traced. Afterward, the data was used to answers the problem statement. The results of the study conclude that the procurement process of gamelan in Tanah Abang village went through a challenging process, however; the impact that follows is quite satisfying since it brings benefits to the community and the village. The process is described through a chart to facilitate understanding. Furthermore, another important point that can be taken from the existence of a set of gamelan musical instruments is social values that can be implemented in everyday life.